2020
DOI: 10.1002/eap.2117
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical multi‐grain models improve descriptions of species’ environmental associations, distribution, and abundance

Abstract: The characterization of species’ environmental niches and spatial distribution predictions based on them are now central to much of ecology and conservation, but implicitly requires decisions about the appropriate spatial scale (i.e., grain) of analysis. Ecological theory and empirical evidence suggest that range‐resident species respond to their environment at two characteristic, hierarchical spatial grains: (1) response grain, the (relatively fine) grain at which an individual uses environmental resources, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 106 publications
0
19
0
Order By: Relevance
“…responses to environmental resources such as foraging [see section 3]) or at coarser scales, such as their broad home range (introduced in section 4) (Mertes et al 2020). Fine and coarse spatial grains have been termed "response grain" and "occupancy grains", respectively (Mertes et al 2020). To quantify an animal's response grain, first passage time analysis can be employed.…”
Section: Meta-ecosystem Models To Understand Animal-vectored Subsidiesmentioning
confidence: 99%
See 2 more Smart Citations
“…responses to environmental resources such as foraging [see section 3]) or at coarser scales, such as their broad home range (introduced in section 4) (Mertes et al 2020). Fine and coarse spatial grains have been termed "response grain" and "occupancy grains", respectively (Mertes et al 2020). To quantify an animal's response grain, first passage time analysis can be employed.…”
Section: Meta-ecosystem Models To Understand Animal-vectored Subsidiesmentioning
confidence: 99%
“…To quantify an animal's response grain, first passage time analysis can be employed. These are defined as the time it takes an animal to cross a circle with a defined radius --and as such scale dependent --and can quantify the time duration of an individual animal present within such a circle (Fauchald & Tveraa 2003) (Johnson 1980;Mertes & Jetz 2017;Mertes et al 2020) should drive the spatial resolution of remote sensing products selected for analysis, not the other way around. This is especially relevant for animal movement data, which are typically measured at finer spatio-temporal resolutions than data from remotely sensed imagery (Remelgado et al 2017(Remelgado et al , 2019.…”
Section: Meta-ecosystem Models To Understand Animal-vectored Subsidiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This should be favour over using an average of the climatic conditions over the sampling period (36,96) or any larger period of time (as Worldclim climatic data from 1950 to 2000 which are commonly used for species distribution modelling (97, 98)). Previous studies already suggested the use of multi-grain approaches involving various spatial resolutions to consider variables affecting the presence of a species at different scales (99)(100)(101). This adds to the recommendation of using data based on species on November 2, 2020 by guest http://aem.asm.org/ Downloaded from ecology rather than on availability (100,102).…”
Section: On the Importance Of Considering The Spatial And Temporal Scmentioning
confidence: 99%
“…These are defined as the time it takes an animal to cross a circle with a defined radius --and as such scale dependent --and can quantify the time duration of an individual animal present within such a circle (Fauchald & Tveraa 2003). (Johnson 1980;Mertes & Jetz 2017;Mertes et al 2020) should drive the spatial resolution of remote sensing products selected for analysis, not the other way around. This is especially relevant for animal movement data, which are typically measured at finer spatio-temporal resolutions than data from remotely sensed imagery (Remelgado et al 2017(Remelgado et al , 2019.…”
Section: (1) Spatial Trophic Structurementioning
confidence: 99%